Modest algebraization a perspective direction of initial mathematical teaching - Bronius Balčytis (Lietuvos Matematikos Rinkinys)
The paper discusses changes in the attitudes towards the content of Mathematics in primary school between 1960 and 1990, on what level letters were used as mathematical symbols, how much the basics of Algebra were taught. By generalizing school practice in a number of countries, such as Germany, England, Italy, Denmark, Latvia, Lithuania and a few others a conclusion is arrived at that teaching of basics of Algebra should be expanded and not narrowed. That would provide wider opportunities for choosing tasks prompting a more speedy teaching of the whole course on mathematics and developing pupils abstract thinking. That is why extra experimenting would be advisable on these issues.